BetaSys 2011
DOI: 10.1007/978-1-4419-6956-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance Spectroscopy

Abstract: In the context of biology, electrical phenomena are usually identified with ionic currents through protein channels, for example as they are postulated during nerve signalling (Andersen et al. Prog Neurobiol 88(2):104-113, 2009; Sakmann and Neher Annu Rev Physiol 46:455-472, 1984). However, there are more electrical phenomena that play a significant role in biological systems, namely those arising from polarization effects (Grimnes Bioimpedance and Bioelectricity, 2008; Polk Handbook of Biological Effects of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 129 publications
(192 reference statements)
0
9
1
Order By: Relevance
“…In comparison to previous work cited earlier, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] we note that the work reported here differs primarily in the concentration on a single parameter classification scheme (the Cole relaxation frequency) and the subsequent need to separate Cole frequencies from samples of mixed tissue types, or nonperfect tissues. Jossinett and Schmitt, 8 Wang et al, 11 and Chauveau et al 9 all describe various types of tissue components found in the breast.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In comparison to previous work cited earlier, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] we note that the work reported here differs primarily in the concentration on a single parameter classification scheme (the Cole relaxation frequency) and the subsequent need to separate Cole frequencies from samples of mixed tissue types, or nonperfect tissues. Jossinett and Schmitt, 8 Wang et al, 11 and Chauveau et al 9 all describe various types of tissue components found in the breast.…”
Section: Discussioncontrasting
confidence: 56%
“…Each of the dispersion regions is attributed to different frequency dependent phenomena in the tissue. 6 Schwan identified 12 biomaterial elements that can be probed by bioimpedance measurements in the various dispersion regions (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…6). According to Kell (1987) and Klösgen et al (2011) each semicircle arc in Fig. 6 revealed a dielectric relaxation of Debye type, i.e.…”
Section: Dielectric Relaxations On Spectrin and Band 3 Of Triton-x-10mentioning
confidence: 83%
“…Based on the theory of dielectroscopy (Kell 1987;Klösgen et al 2011) the frequency dependences of corrected amplitudes ΔZ re and ΔZ im were studied plotting the -ΔZ im vs. ΔZ re for each denaturation temperature, T A and T C . Complex plane (Nyquist) plot of -ΔZ im vs. ΔZ re , determined at the spectrin denaturation temperature, T A , had the form of a semicircle arc, situated below the argument axis (Fig.…”
Section: Dielectric Relaxations On Spectrin and Band 3 Of Triton-x-10mentioning
confidence: 99%
See 1 more Smart Citation